Ecosystem services the dry forest of parroquia Cazaderos, Zapotillo canton, Loja province, Ecuador - Díaz, Marjorie; Villamagua, Gabriela; Pacheco, Edwin; Ochoa, Diana; Quito, Jhulissa (Bosque (Valdivia), 2024)
The dry forest of parroquia Cazaderos located in the southwest of Ecuador, has become a fragile and vulnerable ecosystem due to its productive activities, such as, the traditional use of the forest for goat grazing. In light of this problem, the objective of the present research was to characterize the ecosystem services offered by the forest. The proposed methodological approach was founded on the classification of ecosystem services based on the Millennium Ecosystem Assessment framework. From this classification, it was determined that the dry forest provides supply, regulation and cultural ecosystem services in parroquia Cazaderos. In the supply services, the following were characterized: the supply of fresh water for human consumption, non-timber forest products (medicinal, oils, fibers, dyes and crafts) and timber forest products with endemic and representative species of the dry forest. As regulation services, areas with surface water recharge potential and riparian protection areas were characterized. As cultural services, cultural heritage, feeling of belonging, ecotourism, and scenic beauty were characterized. In this sense, it is concluded that the dry forest is an ecosystem with potential for the provision and maintenance of these services, making it essential to implement protection and conservation actions.